PEMBUATAN EDIBLE FILM BERBAHAN DASAR LIMBAH KULIT SINGKONG DENGAN PENAMBAHAN GLISEROL DAN KITOSAN SEBAGAI PENGEMAS BUMBU BUBUK MIE INSTAN - , ANDHIKA MAYASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research is to increase the potency of cassava peel waste as edible film for instant noodle seasoning wraps and to give better protection. This research includes 2 parts. The first part is the forming of edible film by combining the concentration of cassava peel starch (2 g, 3 g and 4 g) and glycerol (20%, 30% and 40%). The second part is varying the concentration of cassava peel starch (2 g, 3 g and 4 g) by adding the chitosan concentration (0,5 g and 1 g). The tests conducted in this research are : thickness, tensile strength, elongation, water vapor transmission rate (WVTR), scanning electron microscopy (SEM), solubility and biodegradability tests. Edible film from 4 g cassava peel starch by adding 1 g chitosan has the best vapor barrier at 5,9313 g/m 2 /hour. The highest tensile strength value (14,0456 MPa) of edible film is obtained from cassava peel starch film with the variation of 2 g cassava peel starch and 1 g chitosan. The highest elongation value of edible film is 47,6063% by the variation of 4 g cassava peel starch with 1 g chitosan. Biodegradability tests conducted for 3 weeks shows that the film without chitosan is degradated totally in the third week and film with chitosan shows physical changes but not degradated totally in the third week. Scanning electron microscopy (SEM) shows the microstructure morphology of the cassava peel starch film. Without chitosan, the film is not compact and has large pores and brittles on the film surface. The film with chitosan shows the different result compared to the film without chitosan. With chitosan, the film is more compact, has little pores and little brittles on the film surface.